Developing relationships, personalization, and data herald in marketing 5.0 - Kaur, Jasmine, 1987-; Jindal, Priya, 1978-; Singh, Amandeep, 1982- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2022)
"This book explores the changes in modern marketing that is leveraging the unique capabilities of new interactive media to create a new form of interactions and transaction between consumers and marketers, and satisfy the needs of the marketing"--